2022
DOI: 10.1186/s12913-022-07493-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating factors that influenced the successful implementation of an evidence-based neonatal care intervention in Chinese hospitals using the PARIHS framework

Abstract: Background Evidence based interventions (EBIs) can improve patient care and outcomes. Understanding the process for successfully introducing and implementing EBIs can inform effective roll-out and scale up. The Promoting Action on Research Implementation in Health Services (PARIHS) framework can be used to evaluate and guide the introduction and implementation of EBIs. In this study, we used kangaroo mother care (KMC) as an example of an evidence-based neonatal intervention recently introduced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Previous research shows many factors influencing the use evidence-based interventions among neonates including patients, healthcare professionals, and organizational factors ( Cheng et al, 2017 ; Ismail, 2016 ). For example, a study from China found that clinical experience of healthcare professionals, culture of work, leadership characteristics, existence of evaluation and facilitation processes have impact on the implementation of evidence-based interventions such as interventions related to neonatal pain management ( Yue et al, 2022 ). Even though the use of oral sucrose 24% is considered standard practice in many countries, NICU nurses in Saudi Arabia reported minimal use of sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research shows many factors influencing the use evidence-based interventions among neonates including patients, healthcare professionals, and organizational factors ( Cheng et al, 2017 ; Ismail, 2016 ). For example, a study from China found that clinical experience of healthcare professionals, culture of work, leadership characteristics, existence of evaluation and facilitation processes have impact on the implementation of evidence-based interventions such as interventions related to neonatal pain management ( Yue et al, 2022 ). Even though the use of oral sucrose 24% is considered standard practice in many countries, NICU nurses in Saudi Arabia reported minimal use of sucrose.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, although policymakers and decision-makers tried to provide assistance and intervention programs for healthcare workers, they did not anticipate these barriers to attendance. Of course, the support from hospital administrators and leadership could provide more space and human resources to provision KMC, optimize or update the staffing configuration of neonatal care nurses, strengthen the professionalization of neonatal care by healthcare workers, and improve healthcare staff’s attitudes towards and perceptions of KMC [ 43 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors stated that due to lack of space, during the study period of March 2019 to July 2020, only 209 of the eligible 319 infants were admitted into the KMC area. 20 Physical space limitations were also identified as a barrier for implementing KMC, [22][23][24][25] FICare, 21 , 26 NIDCAP, 27 , 28 and infant massage. 29 Another commonly cited barrier to implementation of ERH interventions was the already heavy workloads of healthcare providers (HCPs), which included physicians, nurses, and therapists.…”
Section: Barriersmentioning
confidence: 99%
“…A positive relationship and communication between parent and staff were facilitators toward the implementation of FICare 21,32 and KMC. 19,20,22 HCPs perceiving the intervention as beneficial to patients and families was also a facilitator to implementation. In a study of implementing a FICare/ zero-separation NICU model in the Netherlands, the authors found that the staff's understanding of the importance of the zero-separation, parent- involved model of NICU care was a facilitator and helped them coach and encourage parents.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation